Microenvironment filtering and plant competition jointly structure trait distributions across co-occurring individuals - Mingshan Xu (Elsevier, 2021)
The prevailing role of environmental filtering in community assembly has been widely corroborated at large spatial scales. However, how environmental filtering and plant competition collectively determine trait distributions among coexisting individuals at within-community scales remains an unresolved question. We measured four leaf and wood traits of 2700 co-occurring plants and soil physicochemical and topographic variables across individual locations within a 1 ha subtropical forest in eastern China. Multiple linear regression and variance partitioning analyses were conducted to test the relative effects of microenvironment properties and plant competition on trait distributions (e.g., mean, range, variance, skewness, and kurtosis) at four within-community spatial scales. The joint explanatory power of microenvironment properties and plant competition on trait distributions significantly enhanced with increase of spatial scales. The relative effects of plant competition on trait distributions were more pronounced at smaller scales, and the relative effects of microenvironment properties on trait distributions were remarkable at larger scales. Plant competition at smaller scales and microenvironment filtering at larger scales generated both convergence and divergence of four functional traits. Fertile soils selected for plants with large leaf area and high leaf phosphorus but low nitrogen contents and wood density. Steep and convex locations supported plants with large leaf area and low leaf nitrogen and phosphorus contents, and low wood density. Wet soils supported plants with high leaf nitrogen content and wood density, and low leaf phosphorus content. Acidic soils selected for plants with small leaves and high leaf nitrogen and phosphorus contents. These results provide strong evidence that relative to plant competition, microenvironment filtering is also a predominant driver of individual-level functional diversity and species assemblages at within-community scales. Our study highlights that simultaneously accounting for the consequences of microenvironment heterogeneity and plant competition on trait distributions is crucial for better understanding community assembly of locally co-occurring individuals.